Expanding mechanistic models to represent purple phototrophic bacteria enriched cultures growing outdoors. (1st February 2023) - Capson-Tojo, Gabriel; Batstone, Damien J.; Hülsen, Tim
Highlights: A model was developed to represent outdoors PPB mixed systems. Relevant clades, metabolic routes and environmental conditions were considered. The model included light and temperature dependence and aerobic conditions. The model was calibrated and validated using experimental pilot data. Simulations suggest optimal reactor design and working conditions/strategies. Abstract: The economic feasibility of purple phototrophic bacteria (PPB) for resource recovery relies on using enriched-mixed cultures and sunlight. This work presents an extended Photo-Anaerobic Model (ePAnM), considering: (i) the diverse metabolic capabilities of PPB, (ii) microbial clades interacting with PPB, and (iii) varying environmental conditions. Key kinetic and stoichiometric parameters were either determined experimentally (with dedicated tests), calculated, or gathered from literature. The model was calibrated and validated using different datasets from an outdoors demonstration-scale reactor, as well as results from aerobic and anaerobic batch tests. The ePAnM was able to predict the concentrations of key compounds/components ( e.g., COD, volatile fatty acids, and nutrients), as well as microbial communities (with anaerobic systems dominated by fermenters and PPB). The results underlined the importance of considering other microbial clades and varying environmental conditions. The model predicted a minimum hydraulic retention time of 0.5 d −1 . A maximum width of 10 cm in flat plate reactors should not be exceeded. Simulations showed the potential of a combined day-anaerobic/night-aerobic operational strategy to allow efficient continuous operation. Graphical abstract: Image, graphical abstract